1989
DOI: 10.1111/j.1365-2621.1989.tb04695.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Degradation of Titin and Nebulin of Beef Steaks Varying in Tenderness

Abstract: Purified myofibrils were isolated from "tender" and "less-tendcry' bovine fongissimw muscle at death and at 1, 3, 7, and 14 days of postmortem storage (4°C). Sodium dodecyl sulfate polyaclylamide gel electrophoresis (SDS-PAGE) was used to detect changes in the myofibrillar/cytoskeletal proteins, titin and ncbulin. Titin and nebulin bands were observed to be less intense on gels from "tend& than from "less-tender" steaks. These results suggest that titin and nebulin were more rapidly degraded in "tender" than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 12 publications
1
27
0
1
Order By: Relevance
“…(1997). The previous work of Anderson and Parrish (1989) demonstrated that the degradation of titin and nebulin coincided with increased tenderness because their degradation may alter the integrity of muscle cell (Robson et al. 1991) and decrease the myofibrillar strength (Horowits et al.…”
Section: Discussionmentioning
confidence: 99%
“…(1997). The previous work of Anderson and Parrish (1989) demonstrated that the degradation of titin and nebulin coincided with increased tenderness because their degradation may alter the integrity of muscle cell (Robson et al. 1991) and decrease the myofibrillar strength (Horowits et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other myofibrillar proteins such as titin and nebulin are also implicated in post mortetn weakening of fish (Tsuchiya et al 1992) and meat muscle (Anderson and Parrish 1989). Another study (Astier et a1 1991) using dorado myofibrils showed complete aactinin release and marked titin and nebulin cleavage.…”
Section: Introductionmentioning
confidence: 93%
“…The fact that titin serves such a critical structural role strongly argues that titin degradation may occur more rapidly in muscle tissue of more tender retail cuts than those that are less tender and may be a more useful predictor of tenderness. Although previous studies have evaluated the role of titin in postmortem proteolysis and tenderness development (Anderson and Parrish, 1989;Fritz et al, 1993;Huff-Lonergan et al, 1996), the relationship between proteolysis of this protein and 989 sarcomere length has not been adequately addressed. Therefore, the aim of this work was to determine the role of sarcomere length on the postmortem degradation of titin.…”
Section: Introductionmentioning
confidence: 96%